Husband’s involvement in wife’s antenatal care visits in Indonesia: What factors are related? - Agung Dwi Laksono, - (Page Press, 2022)
Background: Involving husbands in maternal and child health programs can reduce maternal morbidity and mortality. The study aimed to analyze the factors related to the husband’s involvement in antenatal care (ANC) visits in Indonesia. Methods: The study was a cross-sectional study. The research employed secondary data from the 2017 Indonesian Demographic and Health Survey. The analysis units were wives aged 15–49 years old, married, and pregnant in the past 5 years, and the final samples obtained were 14,319 respondents. In addition to the husband’s involvement were residence, age, education, occupation, wealth, and parity. The study used a binary logistic regression test in the final stage. Results: Husbands who lived in urban areas have odds of being involved in ANC visits 1.2 times greater than those in rural areas. The better the husband’s education was, the more involved they were in ANC. The results show husbands who work in any field were better at being involved in ANC. Poorer husbands had odds of being engaged in ANC visits 2.0 times more likely than the husbands’ lowest group. The most prosperous husbands have odds of being involved in ANC visits 5.4 times than the poorest husbands. The husbands’ wealth is better, the more the husbands were engaged in ANC. The more children were born, the less frequent the husbands’ involvement in ANC is. Conclusion: The study concluded five variables associated with husbands’ participation in ANC in Indonesia, including residence, education, occupation, wealth, and parity.